In ostaggio del virtuale sulle tracce di Baudrillard - Specchio, Valerio (Fuori collana, 2023)
During an era in which the main form of recognition would seem to be entrusted to the screen, Jean Baudrillard's reflections offer extremely useful interpretative tools to understand the neo-existence of the screened individual. According to the French philosopher, the simulation, as a codification of entities in a data flow, can be interpreted as a informatic potlatch, a ritual shortcircuit, fueled by the consumption of bits as the ultimate guarantee of persistence. This practice would envelop the entire society in a claustrophobic suspension, smoothing out any possibility of contact, bringing out the user as a transmission channel of an empty signifier: the digital code. The surface of the screen, exposing a sort of ontological indigestion between the individual and his digital projection, would find its own matrix in the intersection between the metaphysical problem and the political question through the figure of the hostage. The screen-society, from the shining call to entertainment, would turn upside down in a saving form of disappearance, reconfiguring a world in which the antiquated shadows of reality would have sharpened into ghosts that had become more real than reality, hyperreal. Precisely starting from this fissure, from this mingling of virtuality and reality, that seems to emerge the urgency of a thought that, as Baudrillard wanted, can transmit the resistance of an elusive singularity.